Case study for effects of pile installation on existing offshore facilities in brownfields - Reda A.; Amaechi C.V.; Shahin M.A. (Elsevier Ltd, 2024)
New prop structures are meant to be used to strengthen existing ageing offshore platforms in brownfields. This technical note aims to assess the possible effects of pile installation of new prop structures on existing offshore facilities, specifically existing platform piles and nearby pipelines. Based on the case study presented, this work investigates the down-drag and interaction effects of installation-induced vibrations of new piles on the load-displacement response of existing piles, namely pile load-bearing capacity and settlement, as well as assessing vibration levels in the vicinity of existing pipelines. 2023 Elsevier Ltd